2019
DOI: 10.1186/s12879-019-4146-5
|View full text |Cite
|
Sign up to set email alerts
|

Invasive meningococcal disease in patients with complement deficiencies: a case series (2008–2017)

Abstract: Background To describe patients with inherited and acquired complement deficiency who developed invasive meningococcal disease (IMD) in England over the last decade. Methods Public Health England conducts enhanced surveillance of IMD in England. We retrospectively identified patients with complement deficiency who developed IMD in England during 2008–2017 and retrieved information on their clinical presentation, vaccination status, medication history, recurrence of infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
1
32
0
2
Order By: Relevance
“…Unlike most previously reported outbreaks of invasive meningococcal disease that were associated with serotype B [20], we found that all our cases of meningococcal meningitis were sporadic. According to other studies, L. monocytogenes is the third most common causative agent of CABM and is associated with older age and immunodeficiency [15,[21][22][23][24]. In our study, L. monocytogenes meningitis was the third most common etiological factor and 40% of L. monocytogenes meningitis in our study occurred in adults under the age of 50 without specific risk factors.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Unlike most previously reported outbreaks of invasive meningococcal disease that were associated with serotype B [20], we found that all our cases of meningococcal meningitis were sporadic. According to other studies, L. monocytogenes is the third most common causative agent of CABM and is associated with older age and immunodeficiency [15,[21][22][23][24]. In our study, L. monocytogenes meningitis was the third most common etiological factor and 40% of L. monocytogenes meningitis in our study occurred in adults under the age of 50 without specific risk factors.…”
Section: Discussionsupporting
confidence: 61%
“…The strongest risk factors in our study for an unfavorable outcome were an older age, coexisting pneumonia and a low platelet count at presentation. According to other studies, impaired consciousness, low white-cell count, a delay in antibiotic therapy initiation and other comorbidities may also lead to a more severe course of meningitis [21,22,31,43].…”
Section: Discussionmentioning
confidence: 96%
“…An additional interference between COVID-19 and IMD may originate from the use of anti-complement drugs that are explored to control COVID-19 by lowering complement mediated pro-inflammatory response [ 16 ]. These drugs such as anti-complement compounded 5 (C5) are known to increase the risk for IMD [ 17 ].…”
Section: Main Textmentioning
confidence: 99%
“…This includes disease caused by unencapsulated strains, such as the US_NmUC strain, that would not normally cause disease in healthy individuals [15]. These individuals are recommended to receive meningococcal vaccination and long-term penicillin prophylaxis [16]. To account for the existence of relatively rare penicillin-resistant strains, ciprofloxacin may also be prescribed as a back-up should the patient experience symptoms of invasive meningococcal disease.…”
Section: Implications Of the Emergence Of Meningococci Adapted To Thementioning
confidence: 99%